Population and Coservation of Macaca fascicularis for Ecotourism Contributing on Sekaroh Forest Area, East Lombok Regency - M. Yamin; Karnan Karnan; Khairuddin Khairuddin (Jurnal Biologi Tropis, 2022)
The Sekaroh Forest Area is one of the fastest growing tourist destinations. This study aims to obtain an accurate description of the population, abundance, food and food sources as well as habitat conditions. Population data of Macaca fascicularis was taken through a census by exploring, observing and observing the type of habitat. Food and food sources, especially those from vegetation elements, were taken using the quadratic method at the observation station. The data obtained were analyzed qualitatively and quantitatively. The results of the study found that the population of Macaca fascicularis in the Sekaroh Forest Area, East Lombok Regency, amounted to 92 individuals. Monkeys consume 33 types of plants, 4 types of insects and are very dependent on the availability of food in their environment, the food provided by visitors is liked by monkeys and provides good nutritional value. Residents in the Sekaroh Forest Area consider the presence of Macaca fascicularis as an agricultural pest. In addition, the population of Macaca fascicularis needs to be controlled as an effort to mitigate agricultural pests and support ecotourism. Local residents need to be involved in Macaca fascicularis conservation efforts in the Sekaroh Forest Area for security and to avoid conflict.